Autism Spectrum Disorder Related Functional Connectivity Changes in the Language Network in Children, Adolescents and Adults - Lee, Yubu; Park, Bo-yong; James, Oliver; Kim, Seong-Gi; Park, Hyunjin (Frontiers in Human Neuroscience, 2017)
Autism spectrum disorder (ASD) is a neurodevelopmental disability with global implication. Altered brain connectivity in the language network has frequently been reported in ASD patients using task-based functional magnetic resonance imaging (fMRI) compared to typically developing (TD) participants. Most of these studies have focused on a specific age group or mixed age groups with ASD. In the current study, we investigated age-related changes in functional connectivity related measure, degree centrality (DC), in the language network across three age groups with ASD (113 children, 113 adolescents, and 103 adults) using resting-state fMRI data collected from the autism brain imaging data exchange repository. We identified regions with significant group-wise differences between ASD and TD groups for three age cohorts using DC based on graph theory. We found that both children and adolescents with ASD showed decreased DC in Broca’s area compared to age-matched TD groups. Adults with ASD showed decreased DC in Wernicke’s area compared to TD adults. We also observed increased DC in the left inferior parietal lobule and left middle temporal gyrus for children with ASD compared to TD children and for adults with ASD compared to TD adults, respectively. Overall, functional differences occurred in key language processing regions such as the left inferior frontal gyrus and superior temporal gyrus related to language production and comprehension across three age cohorts. We explored correlations between DC values of our findings with Autism Diagnostic Observation Schedule (ADOS) scores related to severity of ASD symptoms in the ASD group. We found that DC values of the left inferior frontal gyrus demonstrated negative correlations with ADOS scores in children and adolescents with ASD. The left superior temporal gyrus showed significant negative correlations with ADOS scores in adults with ASD. These results might shed light on the language network regions that should be further explored for prognosis, diagnosis, and monitoring of ASD in three age groups.